DESKRIPSI PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN LIMBAH TAHU DAN PEMANFATAANYA DI KECAMATAN KARANGPLOSO KABUPATEN MALANG - Purwaning Budi Lestari; Moh. Ali Muarifudin; Tri Asih Wahyu Hartati (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2021)
The purpose of this study was to describe the public's perception of tofu waste management and its utilization in Malang Regency. The type of research used is survey research which is analyzed using descriptive statistics by looking at the percentage. The population used is residents around the Jaya Sari tofu factory, Sari Abadi, UD Lancar Jaya, and LW in Karangploso District, Malang Regency. While the instruments for data collection are interview questionnaires and documentation. Based on the description of the results of public perceptions, the highest percentage of perceptions is the question indicator no. 15 of 93.3%, which is about the need for socialization to the community about the use of water hyacinth plants and fish cultivation as an alternative to the use of tofu liquid waste.